Caminhos para a construção de escolas democráticas: atividades educativas diversificadas desenvolvidas em escola pública municipal da cidade de São Paulo - Martins, Valéria Rufino (2017)
The Portuguese colonization left a legacy of deep authoritarianism in the Brazilian society and so democratic experiences, from the political perspective, are incipient. These facts challenge us to think about the role of the school in constructing identities committed with the common good and a fairer society. Faced with this problem, The present research aims to analyze diversified educational activities developed in a public school in the city of São Paulo, and to investigate its influence in the school curriculum and in the implementation of democratic relations toward the construction of a democratic school aiming the Social transformation. The guiding frameworks of this research are the idea of democratic education in the historical moment we live and the role of the public policies in the process of building democratic schools. Our theoretical framework is based on the Critical theory, and aligned with it we have the central question: Can the implementation of diversified cultural projects help the public school to become more democratic? This study aims specifically to identify pertinent educational policies at federal and municipal level referring to elective courses in schools, as well as to describe and characterize democratic relationships and evaluate student participation. This qualitative investigation combines field research, carried out in a public school in the city of São Paulo, and semi-structured interviews with managers and teachers from that school about the educational activities and the coexistence in the school space. Combined with it, a documental analysis was used in order to verify the consonance between the assessed and the proposals contained in the official documents of the school, particularly the Political-Pedagogical Project. The results allowed us to have knowledge of activities developed in the investigated school just as the "Mais Educação São Paulo" program and the identification of experiences of effective student participation. The perceived internal contradictions signals the viability of in-service training. While external public policies make it difficult to develop diversified pedagogical projects and activities by imposing a strict time management and external evaluations which influences and affects the school curriculum